1997
DOI: 10.1007/s11664-997-0240-3
|View full text |Cite
|
Sign up to set email alerts
|

Glancing-angle ion bombardment for modification and monitoring of semiconductor surfaces

Abstract: Using glancing-angle ion bombardment for surface modification rather than conventional near-normalincidence ions has the advantages of reducing damage and implantation projected ranges, reducing channeling, reducing sputtering, and preferentially removing surface asperities leading to flat surfaces. The effects of bombardment conditions on the surface morphology and perfection of GaAs (001), InP (001), and Si (001) surfaces are reported. Air-exposed surfaces were cleaned and smoothened to near atomic flatness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Chason et al [17] have shown that near-normal incidence ions modify RHEED oscillations by creating surface vacancies that can annihilate with deposited adatoms. However, the vacancy creation is associated with sputtering, and sputter yields are very low for small f as discussed above [6,7]. Thus, the ion-induced change in Fig.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Chason et al [17] have shown that near-normal incidence ions modify RHEED oscillations by creating surface vacancies that can annihilate with deposited adatoms. However, the vacancy creation is associated with sputtering, and sputter yields are very low for small f as discussed above [6,7]. Thus, the ion-induced change in Fig.…”
mentioning
confidence: 91%
“…However, these studies suggest unique possibilities for film growth. In particular, glancing-incidence ions are mostly reflected rather than penetrating at flat defect-free portions of a surface, resulting in minimal ion damage, gas entrapment, or sputtering [6,7]. On the other hand, the ions can transfer considerable momentum to surface defects.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The sputtering process has been the subject of both scientific investigations for a long time and recent rapid developing micro‐ and nanotechnologies. Processes such as plasma etching and sputter deposition that involve ion bombardment at relatively low (~ 100 eV) ion energies are widely used in semiconductor processing . However, using glancing‐angle ion bombardment for surface modification rather than conventional near‐normal incidence allows expanding the energy range up to ~10 keV and has the advantages of reducing damage (such as crater formation) leading to extremely smooth surfaces .…”
Section: Introductionmentioning
confidence: 99%